Metode Geolistrik Tahanan Jenis untuk Eksplorasi Air Tanah di Gunung Tunak - Muhammad Zuhdi; Agus Wachid Habiburrahman (Universitas Islam Negeri (UIN) Mataram, 2021)
Geoelectricity is a geophysical method that conducted by injecting an electric current into the earth’s interior. This study objected to map aquifer aquifers using the geoelectric method with a Schlumberger electrode configuration consisting of 4 sounding points. The measurement results are then processed with IP2WIN software which produces a real resistivity map as a function of depth. The correlation between sounding points produces a three-dimensional real resistivity map. The results of the study located at Gunung Tunak, Lombok, West Nusa Tenggara, which consists of 4 sounding points show that the aquifer is at a depth of 66.7 meters 31, 2 meters 58, 7 meters and 34, 1 meter respectively, which are displayed comprehensively with 3 dimensional lithology map.